Global Trends of the Teacher Knowledge of Physical Education: A Bibliometric Analysis - Nurhidayah Yaakop; Denise Koh; Ruhizan Mohammad Yasin (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación)
Background: Physical Education is an important subject in the formal education curriculum in Malaysia also the development of teacher professionalism to face the 21st century education. The bibliometric methods can help researchers and educators understand the important of the research. Purpose: The purpose of this study was to explore the bibliometric characteristics of motivation in the field of Physical Education from 1989 to 2021 that try to discover the related research context and topics. Methods: By using the keywords “physical education” and “teacher knowledge”, the bibliographic records and references have been retrieved from the Scopus databases (date of search: July 15, 2022). The data was analysed using Microsoft Excel for frequency analysis, VOSviewer for data visualisation, and Harzing's Publish or Perish for citation metrics and analysis. Bibliometrics' large picture is also provided. Finding: This study analysed the progression of teacher expertise in physical education research, based on source title, country, and institution, and the publication's citation pattern. This document recognises notable researchers. The data show that physical education teacher knowledge has been extensively distributed and has had a significant influence, since the number of publications outside of Europe, in North America and Asia, has grown. Practical implications: The paper will identify the leading trends in the journal in terms of papers, authors, institutions, countries, journals and keywords. This study is useful for obtaining a quick snapshot of what is happening in the journal. Conclusion/ Significant of Study: The findings of this study contribute to our understanding of the global landscape of research on physical education teacher knowledge.